A basis for selecting the most appropriate small specimen creep test type - Hyde, T. H.; Hyde, Christopher J.; Sun, Wei (American Society of Mechanical Engineers, 2014)
Many components in conventional and nuclear power plant, aero-engines, chemical plant etc., operate at temperatures which are high enough for creep to occur. These include plain pipes, pipe bends, branched pipes etc., the manufacture of such components may also require welds to be inserted in them. In most cases, only nominal operating conditions (i.e., pressure, temperatures, system load, etc.) are known and hence precise life predictions are not possible. Also, the proportion of life consumed will vary from position to position within a component and the plant. Hence, nondestructive techniques are adopted to assist in making decisions on whether to repair, continue operating or scrap certain components. One such approach is to use scoop samples removed from the components to make small creep test specimens, i.e., sub-size uniaxial creep test specimens, impression creep test specimens, small punch creep test specimens, and small ring (circular or elliptical) creep test specimens. Each specimen type has its own unique advantages and disadvantages and it may not be obvious which one is the most appropriate test method to use. This paper gives a brief description of each specimen and associated test type and describes their practical limitations. The suitability of each of the methods for determining “bulk” material properties is described and it is shown that an appropriate test type can be chosen.